Functional Disability, Cognitive Impairment, and Depression Following Hospitalization for Pneumonia - Davydow, Dimitry S. (2013)
PURPOSE: To examine if hospitalization for pneumonia is associated with functional decline, cognitive impairment, and depression, and to compare this impairment to that seen following known disabling conditions such as myocardial infarction or stroke. METHODS: We used data from a prospective cohort of 1,434 adults over age 50 who survived 1,711 hospitalizations for pneumonia, myocardial infarction, or stroke drawn from the Health and Retirement Study (1998–2010). Main outcome measures included the number of Activities and Instrumental Activities of Daily Living requiring assistance and the presence of cognitive impairment and substantial depressive symptoms. RESULTS: Hospitalization for pneumonia was associated with 1.01 new impairments in Activities and Instrumental Activities of Daily Living (95%Confidence Interval [CI]: 0.71, 1.32) among patients without baseline functional impairment and 0.99 new impairments in Activities and Instrumental Activities of Daily Living (95%CI: 0.57, 1.41) among those with mild-to-moderate baseline limitations, as well as moderate-to-severe cognitive impairment (odds ratio [OR], 2.46, 95%CI: 1.60, 3.79) and substantial depressive symptoms (OR, 1.63, 95%CI: 1.06, 2.51). Patients without baseline functional impairment who survived pneumonia hospitalization had more subsequent impairments in Activities and Instrumental Activities of Daily Living than those who survived myocardial infarction hospitalization. There were no significant differences in subsequent moderate-to-severe cognitive impairment or substantial depressive symptoms between patients who survived myocardial infarction or stroke and those who survived pneumonia. CONCLUSIONS: Hospitalization for pneumonia in older adults is associated with subsequent functional and cognitive impairment. Improved pneumonia prevention and interventions to ameliorate adverse sequelae during and following hospitalization may improve outcomes.